ALTERNATIVE THERAPY TACTICS: INTEGRATION OF CUPPING THERAPY AND MASSAGE IN MANAGING LOW DENSITY LIPOPROTEIN (LDL) IN HYPERTENSION PATIENTS WITH HYPERCHOLESTEROLEMIA - Lisnawati Lisnawati; Nazaruddin Nazaruddin; Sanatang (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction:Hypertension sufferers with hypercholestrolemia can cause complications from stroke, heart disease and even death. There is a need for a therapeutic approach that can be used by sufferers as an alternative treatment. Objectives:The aim of this research is to analyze the effect of integrating cupping therapy with massage in controlling LDL levels in hypertension sufferers with hypercholetrolemia. Methods:This research is quantitative research with an experimental approach with a pre-post design with control group. The implementation of this research consists of several stages, namely the first stage, namely determining the number of research samples using the Lameshow formula and based on this formula, a sample number of 68 people was obtained which was divided into 2 groups, namely the intervention group and the control group. Results:in group inintervention, there was a difference in the mean at the pretest from 165.76 to 109.03 at the posttest. And the lowest reduction in cholesterol levels was 49,842 and the highest was 63,629. The results of the Paired t test showed a Phi value of 0.0001 < 0.05, which means that the integration of Cupping Therapy with Massage was able to reduce LDL levels in the Intervention Group. Meanwhile, in the Control group, the mean Pretest value was 159.59 and Posttest 158.32. The results of the paired t test showed that the Phi value was 0.107 > 0.05, which means there was no change in Low Density Lipoprotein (LDL) levels in the control group. Conclusions: Based on the results above, it can be concluded that the integration of cupping therapy and massage can reduce LDL levels in hypertension sufferers with complications of hypercholestrolemia.